Interaction between hematopoietic stem cells and mesenchymal stromal cells and the dimorphic fungal pathogen Histoplasma capsulatum: new immunological insights (2022)
ABSTRACT: Adult stem cells, including hematopoietic stem cells (HSC) and mesenchymal stromal cells (MSC), are characterized not only by their regenerative and immunomodulatory capacity but also by their therapeutic potential in various pathologies. Histoplasmosis is a systemic mycosis caused by Histoplasma spp., which occurs mainly in immunosuppressed individuals. This mycosis can present a severe clinical picture with dissemination to various organs, including the bone marrow, and is associated with anemia and pancytopenia. So far, the effect of a possible interaction of istoplasma with stem cells present in the bone marrow is unknown.